Optical response of thin supported palladium films to hydrogen: non-destructive testing for hydrogen detection - Kalli, Kyriacos; Christofidès, Constantinos; Othonos, Andreas S. (My University, 1999)
The properties of thin palladium films on silicon dioxide/silicon substrates are investigated. As the electrical properties of very thin palladium films cannot be measured, due to highly discontinuous nature of the films resulting from the low level of surface coverage, simple laser diagnostic techniques are used. Results showed the changes in the absolute reflectivity of Pd-SiO2 films upon exposure to various concentrations of hydrogen gas as a function of temperature.
Keywords: Metallic films; Hydrogen; Palladium; Silica